(untitled) (TAMADDUN NURI JURNALI, 2024)
This article explores the diverse landscape of educational tasks aimed at fostering listening comprehension skills among learners. Through a comprehensive examination of task types and descriptive aspects, it unveils the intricacies that underpin effective pedagogical strategies in this domain. Drawing upon various methodologies and theoretical frameworks, the article offers insights into the design, implementation, and contextual considerations of these tasks. From structured exercises to authentic interactions, each task type serves a unique purpose in nurturing listening proficiency. By elucidating the taxonomy of educational tasks and examining their empirical evidence, this article equips educators with valuable resources to tailor instructional practices effectively, whether in traditional classroom settings or digital learning environments.